(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Neural tube defects are congenital abnormalities of neural development with a wide spectrum of clinical manifestations. Meningomyelocele a type of spina bifida , in which the spinal cord and meninges protrude through an opening. Early surgical interventions are required to reduce the mortality rate by preventing early cerebrospinal fluid leakage and related infections. Simple closures can repair small defects. Simple closure can be challenging in larger defects, leading to wound dehiscence and subsequent cerebrospinal fluid leakage. This case report discusses the successful use of modified keystone flap repair for large lumbosacral meningomyelocele defects. We report the 18th day of life, term female baby with lumbosacral meningomyelocele, who underwent neural placode reduction with repair of dura followed by modified keystone flap repair to achieve adequate neural closure and prevent subsequent infection. The flap preserved vascularity and decreased the need for complex grafts and revision surgery with no sign of flap necrosis, fistula, or cerebrospinal fluid leakage. This case highlights that modified keystone flap repair is a safe, simple, successful, and versatile technique that can be used to cover large meningomyelocele defects.